The adult table: Chronic intermittent fasting improves β cell health only in adults - Kathrin Maedler; Heena Pahwa (Cell Reports)
Intermittent fasting (IF) improves metabolic health in some individuals but increases health risks in others. Matta et al. now show that IF oppositely affects β cells depending on age: beneficial at old but deleterious at young age.